EXISTENTIALS, A-CHAINS AND RECONSTRUCTION - Hornstein, Norbert (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2018)
This paper provides a new minimalist analysis of existential constructions that reconciles two salient properties: (i) the fact that the local relation between there and its associate mimics the locality involved in movement relations and (ii) the fact that the associate is interpreted where it sits. Assuming that A-chains can only have one visible link at LF, I argue that, due to certain properties of there, reconstruction into the foot of the associate chain is the only option that yields interpretable results.